Development of Moral Education Teaching Materials for Students at Arabic Education Department - Yenni Yunita; Rojja Febrian; Harif Supriyadi; Rani Nofrianti (AL-ISHLAH: Jurnal Pendidikan, 2022)
The role of teaching materials are very crucial in learning as the media and source of information in improving learning effectiveness. Character teaching materials is a set of teaching materials that are used by lecturer in teaching process which can produce students with good behavior, personality and character. The useful of teaching materials or not is depend on the ability of lecturer to implement and develop them in order the steps to develop teaching materials should be mastered. Development of teaching materials based character is developed by considering the content and design of the materials that is used by students at Arabic education department of Islamic religion Faculty. The development of teaching materials has been validated by experts of content and design materials by conducting interview. After being revised, teaching materials has reached the standard of eligibility from the experts’ assessment of content and design material. Based on data analysis of the effectiveness of teaching materials during the trial by distributing questionnaire and analyzed by using SPSS 23 version, it obtained teaching materials was categorized into neutral namely 69.1%. It means at trial activity, the respondents stated teaching materials neither good nor bad. After being revised from experts, the researchers distributed the questionnaire again to look at the effectiveness teaching materials. After being revised, the effectiveness of teaching materials increases to very good category. It can be proved by respondents’ respond namely 51.87 stated very good.